Evaluasi Teknik Operasional dari Kinerja Instalasi Pengolahan Lumpur Tinja di Kota Kendari - Lukman, Renaldo Rasawula; Pratiwi, Yunita Eka; Rosdiana, Rosdiana (Universitas Muhammadiyah Kendari, 2021)
Fecal waste requires treatment (IPLT) that contains pollutant compounds which result in creating damage to the environment or potentially creating pollution. Therefore, we need a performance evaluation to optimize the performance of the Kendari City IPLT. The Kendari City IPLT serves processing of sewage sludge throughout the sub-district with sources from domestic waste processing units and facilities. Sludge desludging is only carried out by 3% of the total septic tank units that must be vacuumed. The purpose of this study is to determine the effectiveness of the performance of the IPLT in treating waste and determine whether the effluent generated from the IPLT has met the specified quality standards. This research method is to compare the effectiveness of Kendari City IPLT conditions with LH Regulation No. 05 of 2014. The BOD content after analysis was 125.1 mg/L and the oil content was 1 mg / l. The Kendari City IPLT treatment unit consisting of an imhoff tank, anaerobic pool, facultative pool and maturation pool in good condition some ponds did not meet the criteria according to the Ministry of Public Works in 1998. The imhoff tank was only 3.7 m (criteria 6-9 m), the anaerobic pool caused odor that can interfere, facultative pool water height of 2.0 m (criteria 1.2 - 2.4 m).